A Review on Segmentation of Moving Object Under Dynamic Condition - Kala, L; Hemavathy, R (International Journal of Computer Sciences and Engineering, 2013)
Detecting and segmenting moving objects in dynamic scenes is a hard but essential task in a number of applications such as surveillance. Most existing methods only give good results in the case of persistent or slowly changing background, or if both the objects and the background are rigid. It is a difficult task to segment the moving object in the existence of dynamic background. Different kinds of methods exist in this paper to solve the problem of motion detection and motion segmentation. This paper tells us about the various methods used to detect objects under dynamic conditions, where each method is explained in brief along with its merits and demerits.